The Relationship Between the Frequency of Independent Anatomy Study and the Anatomy Exam Results of Students of the Faculty of Medicine and Health, Imelda University, Medan - Nurul Sulviani; Inawaty Inawaty; Indah Suhety; Febi Putri Lestari Hutasuhut; Zanurul Rifhan; Teuku muhammad ilzana; Asyrafun Nisa Adelaide; Ibnu arizona; Meldawati Meldawati (Cattleya Darmaya Fortuna, 2025)
This study aims to examine the relationship between the frequency of independent anatomy study and anatomy block exam results among undergraduate medical students. The data analysis revealed a positive and significant correlation between the two variables, with a Pearson correlation coefficient of r = 0.684, indicating a strong relationship. Furthermore, the simple linear regression analysis showed that each increase in the level of independent study frequency contributed to a 4.82-point increase in the anatomy block exam score. These findings suggest that the more frequently students engage in independent anatomy study, the more likely they are to achieve better academic outcomes in anatomy courses